Menumbuhkan Karakter Cinta Tanah Air Melalui Kegiatan Seni Budaya Indonesia Kepada Siswa di Sekolah - Rianto Harianja, Army (Jurusan Pendidikan IPS FKIP UNJA, 2023)
This research is to find out how to foster a sense of love for the homeland in students through Indonesian arts and culture. Love for one's country is important for all Indonesian people. The abundance of Indonesian culture makes it easy for teachers to foster a sense of love for their country. However, nowadays teenagers prefer westernized culture or culture that does not originate from Indonesia. This research aims to ensure that today's teenagers have a deeper feeling of love for their country. The research method used is literature study by reviewing and identifying research in relevant topic areas. The results of the research found that fostering a sense of love for one's country can use various arts and culture that exist in Indonesia. These cultural arts can include traditional dances, batik, wayang and traditional food